LOW ENTHALPY SYSTEMS IN GEOTHERMAL ENERGY - Strojko, Renato (Journal of Energy Technology, 2024)
Geothermal energy is the most available form of energy and is also weather independent (unlike other types of renewable energy). Furthermore, geothermal energy is present almost everywhere, and it is expected that this energy would have a more important role in the near future. However, not all areas in the world have appropriate geothermal resources, so new technologies are being developed using geothermal resources for generating heat and electricity at low temperatures or enthalpy.